High Performance Direct Torque Control of Induction Motor Drives: Problems and Improvements - Nik Rumzi Nik Idris; Tole Sutikno (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
This paper presents some of the main problems, as well as their root causes, of Direct Torque Control (DTC) 3-phase induction motor drive. The high torque ripple in DTC drive due to the hysteresis controller inevitably becomes worst with the discrete implementation of the drive system. The hysteresis controller also causes variable switching frequency that depends on operating conditions, especially the speed. The simplification used in stator flux expression for voltage vectors selection in flux control results in a poor flux regulation at low speed. To overcome these problems, techniques that have been implemented at UTM- PROTON Future Drive Laboratory (UPFDL) are presented and described. Some experimental results obtained from the previous works are also presented and discussed.